PERFECTION OF LEGAL BASIS IN ORGANIZED CRIME’S COMBATING IN UKRAINE. IS IT ENOUGH TO COMBAT ORGANIZED CRIME? - Buciunas, Gediminas (Administrative and Criminal Justice, 2019)
The aim of the paper is to overview and analyze legal basis for combating organized crime in Ukraine, namely international and regional agreements (The Conventions and their additional protocols). The novelty of the paper is the fact that this type of research has not been carried out in depth yet abroad with exceptions on some aspects in Ukraine. This will allow us to have clear picture on legal basis for combating organized crime in Ukraine from international point of view. At the same time it facilitates to get a clear and comprehensive answer for the following questions: is international and regional legal basis enough to combat successfully a public enemy? Does Ukraine have law on prevention organized crime?